(untitled) (Journal of International Studies, 2025)
This study aimed to document, explore, and compare rationales, strategies, and challenges, as well as identify best practices in the internationalisation of several Islamic universities in Indonesia and Malaysia. Drawing on a multiple case study approach, data are sourced by collecting pertinent documents and conducting semi-structured interviews with key informants from public and private Islamic universities in both countries. Data analysis was carried out in two stages. First, the data were analysed separately based on their characteristics. Documents were analysed using document analysis techniques, while data from interviews were examined through thematic analysis. In the second stage, all findings from the first data analysis were collated for a cross-case analysis to identify similarities and differences. The study discovered that both Indonesia and Malaysia aim to address globalisation and enhance their international standing by internationalising their higher education institutions (HEIs). In Indonesia, achieving better academic recognition through internationalisation is a major motivation for Islamic HEIs, especially those seeking a better accreditation status. Although similar motivation is shared by some of the participating Malaysian Islamic HEIs, but achieving academic global prominence has been the major objective of their internationalisation programs. The study also found that the internationalisation strategies of Islamic HEIs in both countries aligned with multiple typologies of internationalisation strategy. However, various challenges hinder the internationalisation efforts of Islamic HEIs in both contexts, including language proficiency, multicultural awareness, the implementation of sustainable and cost-effective internationalisation programs, immigration and international student regulations, as well as inadequate staffing in international offices.